The “Sternhold and Hopkins” Project: A Case Study of the Impact of Translation on Culture, Society, Mentalities, Book Production and Circulation - Baseotto, Paola (Status Quaestionis, 2019)
This article examines an interesting case study of the cultural, social, and ideological functions of translation. My discussion focuses on the most successful editorial initiative in early modern England: the metrical translation of the Book of Psalms by Thomas Sternhold and his followers. Printed in 1,000 editions from its first publication in 1562 to its last in 1828, the “Sternhold and Hopkins” metrical psalter was immensely popular; a million copies were sold by 1640. At the centre of public, personal and family devotion, often appended to the Geneva Bible and the Book of Common Prayer, this translation had a remarkable impact not just on theology, but on literacy and on language, as well as, more broadly, on mentalities and social interactions.